Exploring Theories and Social Policy Changes During COVID-19 Pandemic - Mäntyneva, Päivi (Socialinė teorija, empirija, politika ir praktika, 2024)
The COVID-19 pandemic presented unprecedented challenges to the capacity of developed welfare states to meet emerging needs. In its initial year, the pandemic prompted a wave of new social policy programmes and modifications to existing ones. This study empirically investigates the applicability of various social theories in elucidating the dynamics of social policy changes during the COVID-19 crisis.Reflective analysis employs Hegelian dialectics as a methodological framework on established theories, including welfare regime theory, path dependence theory, path creation, and incorporates contemporary perspectives such as capability theory. The aim is to reflect and discern what these approaches explain and how these theoretical paradigms account for the observed shifts in social policy dynamics.The paper builds on previously published studies focused on the dynamics of persistence and change, mitigation and prevention, divergence and convergence, and continuity and irruption in social policies implemented in response to the pandemic. The article also contributes at developing a theoretical and methodological reflective approach to examine social policy changes in multiple contexts.